(untitled) (Nepal Agriculture Research Journal, 2009)
The study was carried out during June to August 2003, using one hundred and eight day old turkey poults which were randomly divided into twelve groups, 9 birds in each. Three replicate were allocated to each four dietary treatments. Commercially available broiler feed (Ratna feed) was considered as basal diet (Diet-1), Diet-2 was prepared by addition of lysine (0.3%) + methionine (0.1%) to Diet-1, Diet-3 was prepared by supplementation of soybean cake (15%) + lysine (0.2%) + methionine (0.1%) to Diet-1and Diet-4 was formulated by addition of soybean cake (10%) + fishmeal (5%) in Diet-1. Each diet was offered ad lib. from one week to 10 weeks of age. Observation on weekly body weight, weekly and cumulative feed consumed was accessed. Weekly body weight gain and feed conversion ratio was calculated. Economics of dietary treatments in terms of income over chicks and feed cost was also calculated. Significantly higher body weight (P < 0.01) was observed in birds fed with Diet-3 (1881.5 ± 17 g), followed by Diet-4 (1745.3 ± 33 g) and Diet-2 (1460.8 ± 51 g) as compared to Diet-1 (1125.2 ± 20 g) up to 10 weeks of age. The birds fed with supplemented diet consumed significantly (P < 0.01) higher feed than that of basal diet. The average additional profit per bird fed with supplemented diets over basal diet was found to be Rs 31.21, Rs 29.4 and Rs 9.92 for Diet-3, followed by Diet-4 and Diet-2, respectively. The results showed that supplemented diets were more economical than that of basal diet. It may be concluded that supplementation of either soybean cake (15%) along with lysine (0.2%) and methionine (0.1%) or soybean cake (10%) and fishmeal (5%) in commercial broiler ration could be beneficial for enhancing higher body weight of turkey poults and resulted higher gross income as compared to basal diet (broiler ration). Key words: Fishmeal; lysine; methionine; soybean cake; turkey DOI: 10.3126/narj.v7i0.1871 Nepal Agriculture Research Journal Vol.7 2006 pp.70-74